Impact of Corporate Governance Practices on Working Capital Management Efficiency: A Structural Equation Modelling Approach - Goel, Utkarsh; Bansal, Nidhi; Sharma, Anil K. (Indian Journal of Finance, 2015)
Working capital management and corporate governance are two important issues of overall firm management. The purpose of this study was to explore the impact of corporate governance practices on working capital management (WCM) efficiency of firms in a growing economy like India. We used data from 127 large Indian manufacturing sector firms and employed structural equation modelling to study this relationship. The period of the study is from 2004-2013 (10 years). We found that corporate governance indicators like board size, number of independent directors in a board, and percentage of independent members in an audit committee do significantly affect the efficiency of working capital management. We also found that an increase in independence of the board and audit committee compels the management to be conservative in managing short term capital, which in turn negatively affects WCM efficiency. It was observed that an increase in board size weakens control and allows the management to follow aggressive WCM strategies. The results also revealed that the size and independence of a board has more effect on WCM efficiency than the independence of the audit committee. The results of the study will help the practitioners, investors, and analysts to better understand the relation between effective corporate governance and short term funds management and enable them to take better and informed decisions.